The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.4038/cjsbs.v39i1.2350
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the human-elephant conflict in Sri Lanka

Abstract: The association between man and elephant in Sri Lanka is ancient. Elephants being the largest terrestrial herbivores require relatively large areas and diversity of environments to forage. With the increase in human population density and changes in the land-use patterns, elephant habitat is being continuously reduced. As a result, much of the present day elephant range extends into and overlaps with agricultural lands resulting in conflict with man. The assessment of the human-elephant conflict was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 15 publications
5
37
0
Order By: Relevance
“…Across the three study divisions, crop raiding was the most frequently recorded and mentioned HEC. This agrees with a study in Zimbabwe, where crops such as maize and sorghum were found to attract elephants [15] while in Ghana cocoa was most attractive [26]; in India, coffee seemed to attract elephants [27] and in Asia paddy [28]. In our study area, 82% of respondents mentioned maize to be highly preferred by elephants compared to other crops, congruent with findings by [15,29] in Zimbabwe and Tanzania (Serengeti), respectively.…”
Section: Human Perception Human-elephant Conflict Incidents Andsupporting
confidence: 91%
See 2 more Smart Citations
“…Across the three study divisions, crop raiding was the most frequently recorded and mentioned HEC. This agrees with a study in Zimbabwe, where crops such as maize and sorghum were found to attract elephants [15] while in Ghana cocoa was most attractive [26]; in India, coffee seemed to attract elephants [27] and in Asia paddy [28]. In our study area, 82% of respondents mentioned maize to be highly preferred by elephants compared to other crops, congruent with findings by [15,29] in Zimbabwe and Tanzania (Serengeti), respectively.…”
Section: Human Perception Human-elephant Conflict Incidents Andsupporting
confidence: 91%
“…This is relatively high loss compared to other studies like in Cameroon which showed the cost of elephant raiding was 195 USD per ha [33] and in Asia 200 USD per year. Elephant crop raiding (95%) in this study took place during the nights and early mornings, involving both male and female elephants, similar to our study, which is in contrast to findings by [28] that found that mainly solitary bulls attacked crops in Sri Lanka.…”
Section: Human Perception Human-elephant Conflict Incidents Andsupporting
confidence: 84%
See 1 more Smart Citation
“…Even though people and wild elephants live within the same sanctuary, human death and injuries were low compared to other regions in Sri Lanka. For example, Santiapillai et al (2010) revealed human fatalities by elephants in five regions in Sri Lanka; Northwestern, North Central, Central, Eastern and Eva provinces and found that 45 people were killed by wild elephants in 2008, but none were reported from the Central Province. People have a deep knowledge about elephants due to their direct co-existence with elephants in the same area, and know how to save their lives from elephant attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Request permissions from permissions@acm.org. every year [10]. Different efforts have been undertaken to alleviate this conflict, such as the establishment of electric fences, which is, however, not practicable to cover larger areas.…”
Section: Introductionmentioning
confidence: 99%